Polimorfismos no gene do hormônio do crescimento associado a características de crescimento de Tilápia do Nilo - Rodriguez Rodriguez, Maria Del Pilar (2014)
The growth hormone gene (GH) has been a point of study for many researchers because it has been shown that it acts in various physiological processes. Molecular techniques such as sequencing have enabled access to the genomic structure information of GH gene and its polymorphisms, some of these correlated with improved performance and/or production. Tilapia have two GH called GH1 and GH2 their genomic sequences are in the GENBANK database with access numbers of M97766.1 and M97765, respectively, when done the alignment of these sequences we found a high homology. However, there is the repetition of a microsatellite (CTGT) located at two base pairs of the exon 2, the GH1 has seven replications and GH2 has six replications. A pair of specific primers for the GH1 and GH2 genes that amplify a commum region, where the only expected difference are the four base pairs relating to repetition (CTGT) at least, previously described in GH2, shows a difference of approximately 50bp tilapia in some individuals of tilapia, thus defining two types of individuals when using the primer pair, those with a single fragment of 650bp called GHbs (GH single band) and those with two fragments 650pb and 700pb GHbd (GH band double). Given this observation the research objective was to characterize polymorphisms not yet reported GHbs and GHbd by sequencing technique for varieties of GIFT tilapia, Thai, Bouaké and some of its crossings and calculate the frequencies of these polymorphisms . From the results of sequencing GHbs came to be called GH/Ho individuals who are homozygous with the same number of repetitions (CTGT) in GH1 and GH2 and GHbd as GH/He individuals who are heterozygous with different number of repetitions (CTGT) in GH1 and GH2. Thus, the other objectives were to evaluate the relationship between the polymorphisms GH/HO and GH/He with the performance characteristics polymorphisms, assessing the growth of tilapia GIFT x Thai in a period of 150 days and analyze the hyperplastic and hypertrophic growth of white muscle at 30-60-90 and 120 days of age tilapia, being collected right lateral muscle which was insert paraffin for semi-serial cuts and hematoxylin-eosin staining. The results of sequencing revealed that, when made the sequences aliggnments of genotypes GHbs and GHbd these have mutations as transversions, transitions and deletions when compared to the sequences of the GH1 and GH2 genes. It was also described that individuals can be either homozygous (GH/Ho) or heterozygous (GH/He) with respect to the number of the microsatellite repeats (CTGT) in GH1 and GH2. The genotype frequencies in Thai variety and crossing Thai Thai x GIFT showed 50% of GH/HE and GH/Ho, GIFT of fifth generation from a breeding program showed 90% of GH/Ho and crossing GIFT x Bouake (GXB) found up 100% of individuals GH/He. The results of the morphometric and performance was a significant effect of amplification pattern GH/He for final weight (FW), weight gain (WG), total length (TL), head length (CCAB), head weight was observed (PCAB), weight of gutted fish (PPevis) and weight of skinless fillet (pFILE). Histological evaluations of white muscle fibers of the genotypes showed no significant difference in the frequencies for most ages considered. We can conclude that both GH1 and GH2 may have 6 or 7 repeats of microsatellite CTGT, other low-frequency polymorphisms can be found in the studied region of the GH gene in variety GIFT and frequencies of GH/HO or GH/He may be associated with variety. Evaluations of performance the GH/He individuals showed significant differences for some features, however, it takes a study to examine whether there is change in the amino acid or regulatory regions of the GH gene, yet in the growth of white muscle there are no differences between the polymorphisms.